COMPENSATION ON COPYRIGHT DUPLICATION IN PERSPECTIVE OF THE CONCEPT OF ḤAQ AL-IBTIKÂR: A STUDY ON PT ERLANGGA BANDA ACEH CITY - Ova Uswatun Nadia; Chairul Fahmi (JURISTA: Jurnal Hukum dan Keadilan, 2020)
Haq al-ibtikâr as the right to copyrighted works, in shar'i should be protected as intellectual property for the copyright holder. This study aims to determine how the legal efforts made by Erlangga Publishers Banda Aceh City against illegal duplication of books, and how the form of compensation made by Erlangga Publishers Banda Aceh City, as well as a review of the concept of haq al-ibtikâr against compensation on copyright duplication in Erlannga publishers Banda Aceh City. The type of research used is descriptive, data collection is done by library research and field research, data collection techniques by interview and observation. The results obtained that the management of PT Erlangga Banda Aceh City has been maximally to reduce and eliminate various forms of piracy and duplication of its copyright by way of socialisation to the public about the urgency of copyright and evaluation and investigation into various bookstores in Banda Aceh City. Follow-up on duplication is done in the form of a subpoena as a strong warning against copyright infringement by certain parties. Other legal actions in the form of compensation and criminal can not be done optimally because of the limitations of legal remedies that can be done, while in the central management of PT Erlangga efforts to compensate in the form of financial compensation has been done. In the concept of Islam haq al-ibtikâr becomes one of the sources of wealth for the owner and shar'i every wealth is protected from all forms of arbitrariness, so that the owner can bertasharruf according to his wishes.